Using MOODLE as Blended Learning For Assessment in Writing Class - Dita Grace; Widya Caterine (Fakultas Ilmu Budaya, Universitas Brawijaya, 2019)
This research aims to expose about how blended learning transforms into writing class as an assessment. With the changing of technology, the conventional classroom also converts into online class. The students mostly interest on using technology like Moodle , to improve their writing essay. Technically, the teacher also improves in giving materials through online since the face – to – face classroom already giving limitation on the time. By using Moodle, the teacher enables assess the students’ writing through forum, commentator shown between students as peer assessment, teacher’s review, revised the draft, and re-upload the draft.